Interactive digital maps as a project management tool in design: an analysis of the my maps platform - Weber, Karina Pereira; Berlato, Larissa Fontoura; Gonçalves, Berenice Santos; de Figueiredo, Luiz Fernando Gonçalves (Gestão & Tecnologia de Projetos (Design Management and Technology), 2020)
Within the theme of interactive digital maps, as an information visualization interface, this article aims to evaluate the Google My Maps platform. The analysis was based on the principles of information design through the visual variables of Mijksenaar (1997) and mapping methods (LOCH, 2006; ARCHELA; THÉRY, 2008), evaluating its functionalities and conditions for use as a strategic management tool of projects. As results, it is pointed out that the platform is a resource that enhances the visualization of scenarios, system actors, as well as territorial valorization through narratives that can be counted in the descriptions of the mapped projects, although it is somewhat limited to explore the different types of mapping methods. The interactive digital maps, through My Maps, can contribute to the design management process at a strategic level, helping to visualize the information.